How not to design an online pharmacy : A case study - Rauti, Sampsa; Vuorinen, Esko; Carlsson, Robin (United States, 2025)
In today's digitized society, essential web-based healthcare services such as online pharmacies play a crucial role. This paper presents a case study on the third-party services used in an online pharmacy. We perform a network traffic analysis for the pharmacy website, revealing significant data leaks to multiple third parties. We also discuss the potential factors that have led to these privacy flaws and provide recommendations to address the found issues effectively.
ICISE '23: Proceedings of the 2023 8th International Conference on Information Systems Engineering